Do entrepreneurs really earn less? - Alina Sorgner; Michael Fritsch; Alexander Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Based on representative micro data for Germany, we compare the incomes of self-employed with those of wage workers. Our results show that the median self-employed entrepreneur with employees earns significantly more than the median salaried employee, while the median solo entrepreneur earns less. However, solo entrepreneurship pays for those with a university entrance degree but no further professional qualification as well as for those who were in the upper percentiles of the income distribution in their previous salaried job. Surprisingly, the variation in hourly incomes of solo entrepreneurs is higher than that of entrepreneurs with employees.
Keywords: L26; D22; 330; Income; Entrepreneurship; Self-Employment; Start-ups; Germany